Efficiency of university education: A partial frontier analysis - Rafael Antonio Viana; José M. Arranz; Carlos García Serrano (Latin American Economic Review, 2020)
This article investigates the efficiency of the university education using two linked databases (Saber Pro and Saber 11) from the Colombian Institute for Evaluation of Education (ICFES) corresponding to 2014. We use a non-parametric frontier approach that combines the "order m" technique with the concept of a meta-frontier to disaggregate students' total efficiency in generic skills in quantitative reasoning, critical reading, and written communication, into the parts attributable to the students themselves and the university. The analysis is performed by academic programme and by education sector (public vs. private). Results indicate that most of the inefficiency of students in the assessment of generic skills in higher education is attributable to the students themselves and a significant number of students could improve their performance in the assessment in each of the academic programmes if they performed as efficiently as those located on the frontier. Furthermore, the inefficiency share of students varies between academic programmes and university sectors, with students in the private sector more inefficient than those in the public sector in some and less inefficient in others. This research constitutes the first application of the technique of "order m" with the approach of the meta-frontier for the analysis of educational efficiency using data at the student and university levels.
Keywords: C13; C14; I20; I21; 330; efficiency; tertiary education; order m and me-ta-frontier models